Multi-levels AH-MPPM Coding for Indoor Optical Wireless Communications Systems. (2015) - Rouissat, Mehdi; Borsali, Riad
Abstract: The aim of the paper is to present a modified modulation suitable for Indoor Wireless Optical Communications (IWOC)systems that use usually LEDs as transmitter components. As bandwidth of LEDs is times tighter than that of lasers. A modulation that provide high spectral efficiency is desirable, thus we propose Multi-level Anisochronous Harmonic Multi-Pulse Pulse Position Modulation as a modified AH-MPPM modulations for IWOC. This modified modulation has been shown to be a good candidate for IWOC systems that require high data rate and spectral efficiency, especially for those systems that use LEDs. In this paper we present the expressions of band width efficiency, power requirements, and the data rate normalized to PPM, and we also present comparison results to AH-MPPM modulation scheme.